(3GdQjGVjGJ ddGbJUGO h GdYdhe GdGOGQjI h GdeGdjIs - (3MSf jGSjf(B, (3WYeIs ((3YeGf(B:s (3OGQ UaGA(B,s, 2010)
(3GdOhGd h JWHjbGJgG , LHQ GdeUahaGJ h JWHjbGJgG , Md GdfeGPL GdGbJUGOjI HGSJNOGe LHQ GdeUahaGJ , GdfgGjGJ h GdGJUGd , GdeTJbI h JWHjbGJgG , GdJcGed h JWHjbGJg , GdeJhGdjGJ GdYOOjI h JWHjbGJgG h CNjQG feGPL GdHQeLI GdNWjI eY hLhO CSFdI aj fgGjI cd aUd (B.s
(3eQGLY U(B.371s
Keywords: (3GdEbJUGO GdQjGVjs; (3GdQjGVjGJs; (3GdYdhe GdEOGQjIs